PENGARUH LIKUIDITAS, LEVERAGE DAN OPERATING CAPACITY TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN JASA SEKTOR PROPERTI AND REAL ESTATE DI BEI - Muhammad Yusuf; Dadah Muliansyah; Zenzibar (JURNAL LENTERA BISNIS, 2025)
This research aims to study three things: the effect of liquidity on financial distress in companies listed on the Indonesia Stock Exchange in the property and real estate sector; the effect of leverage on financial distress in companies listed on the Indonesia Stock Exchange in the property and real estate sector; and the effect of operational capability on financial distress in companies listed on the Indonesia Stock Exchange in the property and real estate sector.The results show a positive and significant relationship between financial problems, which contradicts the general theory.This may indicate how companies behave when facing a crisis or specific industry or time characteristics.Leverage: This is related to financial issues.Although the direction of the relationship needs to be clarified, its importance is clear.Theoretically, it is likely to have either a positive or negative impact.There are no results showing that someone's financial suffering is significant.